1990
DOI: 10.1161/01.res.66.4.999
|View full text |Cite
|
Sign up to set email alerts
|

Decreased contractile efficiency and increased nonmechanical energy cost in hyperthyroid rabbit heart. Relation between O2 consumption and systolic pressure-volume area or force-time integral.

Abstract: Both systolic pressure-volume area (PVA) and force-time integral (FM1) have been used as measures of oxygen consumption per beat (Vo2) in the isolated left ventricle. The reciprocal of the slope of the Vo2-PVA relation has been considered to reflect the chemomechanical energy transduction efficiency of the contractile machinery (contractile efficiency), whereas its Vo2 intercept consists of energy cost of excitation-contraction coupling and basal metabolism. To examine whether the increase in myosin isoform V1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 45 publications
9
32
0
Order By: Relevance
“…For volume runs, EDP and peak-systolic pressure were plotted against LV volume (pressure-volume diagram). The end-systolic pressure-volume relation (ESPVR) was fitted to a nonlinear equation (2,8,15) …”
Section: Discussionmentioning
confidence: 99%
“…For volume runs, EDP and peak-systolic pressure were plotted against LV volume (pressure-volume diagram). The end-systolic pressure-volume relation (ESPVR) was fitted to a nonlinear equation (2,8,15) …”
Section: Discussionmentioning
confidence: 99%
“…The pressure volume area (PVA) (represented as the total area under the nonlinear ESPVR as well as the systolic segment ofthe pressure-volume trajectory and above the end-diastolic pressure-volume relation curve) was calculated for each beat during caval occlusion by the method of Goto et al (14). Preload recruitable PVA (PRPVA) was defined as the slope of the least-squares linear regression between PVA and EDV: PVA = Mp,,, (EDV-Vp,,), where Mp, and Vp, are the slope and volume intercept, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The slope of the V O 2 -PVA relation remained unchanged in hypothyroid (11) and diabetic (1) rat hearts, whereas a steeper slope of the V O 2 -PVA relation was reported in hyperthyroid rabbit hearts. It was reported that the slope of the V O 2 -PVA relation was related to the ratio of the myosin isoform component from predominantly V3 to predominantly V1 (i.e., the slope of the V O 2 -PVA relation increases when the V1-to-V3 ratio increases, and the slope of the V O 2 -PVA relation is unchanged when the V1-to-V3 ratio decreases) (6). It was also reported that a progressive decrease in V1 and an increase in V3 were apparent in the LV 8-to 16 wk after AV shunt (21).…”
Section: Chemomechanical Energy Transductionmentioning
confidence: 99%